Cytomegalovirus Disease in Children with Acute Lymphoblastic Leukemia: A case series study - İlknur Çağlar; İlker Devrim; Özgür Cartı; Mine Duzgol; Ahu Kara Aksay; Bengü Demirag; Salih Gözmen; Yılmaz Ay; Tuba Hilkay Karapınar; Nuri Bayram; Yeşim Oymak; Canan Vergin (Galenos Publishing House, 2019)
INTRODUCTION: There are limited data focusing on cytomegalovirus (CMV) incidence and manifestations in children with acute lymphoblastic leukemia (ALL) apart from bone marrow transplant recipients. In this study, we review our experience of the manifestations, treatment, and outcome of cytomegalovirus infection in pediatric ALL patients. METHODS: We retrospectively reviewed the clinical characteristics of patients with ALL that were diagnosed with CMV disease while they are on standard chemotherapy. RESULTS: Fourteen patients were included. Fever was the most common symptom (64%). Eyes, lungs and liver were the most commonly involved organs in CMV disease. Lymphopenia was found in most of the patients. At the time of diagnosis, 50% of the patients were on maintenance phase of chemotherapy. All patients were treated with intravenous ganciclovir; two patients died because of concomitant infections, two children with retinitis had permanent visual sequelae and others had a complete recovery. DISCUSSION AND CONCLUSION: In children with ALL, CMV is an important pathogen with serious consequences including retinitis which may be asymptomatic and result in complete visual loss. Not only during intense chemotherapy but also in maintenance phase CMV disease may occur. Especially when prolonged (>7 days) febrile neutropenia and lymphopenia is present, CMV must be kept in mind for differential diagnosis.